Ecofeminist Discourse in Oral Literature: An Analysis of the Sumur Songo Legend in Gresik - Wirawan, Abdul Karim; Abdillah, Khumaidi (Abjad Journal of Humanities & Education, 2025)
Ecofeminism discourse within Indonesian oral literature presents a new dimension in literary studies connecting ecological aspects, feminism, and local wisdom, yet comprehensive analysis applying ecofeminist perspectives to Javanese oral traditions remains limited. This research aims to analyze the construction of ecofeminist discourse in the Sumur Songo legend from Gresik and examine its relevance to Javanese socio-cultural contexts. The study employs a descriptive qualitative approach with ecofeminism theoretical framework, utilizing systematic documentation methods for data collection and qualitative analysis through coding processes encompassing open, axial, and selective coding stages. The research reveals that ecofeminist discourse in the Sumur Songo legend is constructed through complex interplay of women's subjectivity, natural symbolism, and resistance against patriarchal domination, demonstrated through Nyai Ageng Tumengkang Sari's intimate connection with wells as fertility symbols and her sophisticated resistance strategies using local knowledge of Javanese cosmology. The legend's relevance to Javanese socio-cultural context manifests through integration of balance (timbang) and harmony (rukun) concepts, Islamic-Javanese syncretism in coastal Gresik society, and spiritual practices connecting women's power with natural forces. This study concludes that ecofeminist values have been deeply embedded within Javanese cultural tradition, with oral literature functioning as an effective medium for transmitting these values across generations while providing alternative paradigms for sustainable and gender-just development.